Characterising emergency department high-frequency users in a rural hospital. Issue 1 (18th December 2013) - Hardie, Thomas L; Polek, Carolee; Wheeler, Erlinda; McCamant, Karen; Dixson, Melinda; Gailey, Robert; Lafrak, Karen
Abstract : Objective: Patients who are frequent users (≥4 visits/year) comprise ∼10% of patients, but account for ∼34% of total yearly emergency department (ED) visits. Non-emergent care provided to frequent ED users affects operating costs and usage. The majority of reports characterising frequent ED use are from urban teaching centres. This study describes frequent users of ED services in a rural community setting and the association between counts of patient's visits and discrete diagnoses. Design: Retrospective study of 1652 frequent ED adult patients from a rural US hospital over a one-year period. Descriptive statistics and Poisson regression were used to explore the characteristics of frequent users and their patterns of diagnoses. Results: Frequent user visits ranged from 4 to 66 per patient. Frequent users were 9.41% of patient volume accounting for 33.94% of the total visits and were younger compared with patients with <4 visits. Approximately 36% of frequent user visits were generated by 20 diagnoses when the diagnoses were concatenated into domains which covered ∼76% of the visits. There was a high correlation between the number of visits and discrete diagnoses in frequent users. Conclusions: These findings suggest a more complex picture of rural ED services and their relationship with primary care and dental services, which needs to be defined before policy development to reduce ED use.